Green Economy - Temirov Azizbek Voit oʻgʻli (Research Parks Publishers, 2025)
This investigation explores Uzbekistan's conversion to a green economy while filling gaps in knowledge about combined assessments of environmental and economic and social elements for sustainability development. A mixed-methods methodology entailed gathering quantitative data by conducting survey assessments of stakeholders while additionally conducting qualitative interviews with policymakers and industry experts and leadership members. Research findings demonstrated renewable energy together with resource efficiency as opportunities for sustainable development while financial limitations as well as slow institutional changes served as main impediments. According to research findings policymakers must develop specific framework policies and dedicate significant resources toward eco-friendly technology development and launch awareness programs that aim at specific targets. A complete approach to sustainability must become a policy priority to ensure resilient growth inclusive of all populations according to Uzbekistan's specific socio-economic features.